Activation of microglial Toll‐like receptor 3 promotes neuronal survival against cerebral ischemia. Issue 4 (18th December 2015) - Jeong, Si‐Yeon; Jeon, Raok; Choi, Yoon Kyung; Jung, Joo Eun; Liang, Anna; Xing, Changhong; Wang, Xiaoying; Lo, Eng H.; Song, Yun Seon
Abstract: Emerging experimental evidence suggests that activation of Toll‐like receptor 3 (TLR3) by its agonist polyinosinic polycytidylic acid (poly‐ICLC) protects neurons against cerebral ischemia, but the underlying mechanisms remain largely unknown. In the brain, TLR3 is mostly expressed in glial cells. Therefore, we assess the hypothesis that TLR3 activation in microglia is required for neuroprotection against ischemia. After transient focal cerebral ischemia, microglia/macrophages (MMs) demonstrate a significant reduction in TLR3 and its downstream cytokine interleukin 6 (IL‐6). Subsequently, activation of TLR3 by poly‐ICLC restored TLR3 expression and decreased infarction. To further investigate these mechanisms, we turned to a primary cell culture system. Consistent with the in vivo findings, oxygen–glucose deprivation (OGD) significantly reduced TLR3 and IL‐6 mRNA expression in microglia, but poly‐ICLC significantly rescued TLR3 and IL‐6 expression. Importantly, conditioned media from OGD‐treated microglia increased neuronal death after OGD. In contrast, the conditioned media from microglia treated with poly‐ICLC after OGD significantly protected against OGD‐induced neuron death. Taken together, our findings provide proof‐of‐concept that activation of TLR3 in microglia may promote neuron survival after ischemia. We assessed the hypothesis that Toll‐like receptor 3 (TLR3) activation in microglia is required for neuroprotection against ischemia. After transient focal cerebral ischemia, microglia/macrophage demonstrates a reduction in TLR3 and Interleukin 6 (IL‐6). Also, oxygen–glucose deprivation (OGD) reduces TLR3 and IL‐6 expression in microglia, but polyinosinic polycytidylic acid (poly‐ICLC) rescues TLR3 and IL‐6. Importantly, conditioned media from microglia treated with poly‐ICLC protects against OGD‐induced neuron death. We propose that activation of TLR3 in microglia may promote neuron survival after ischemia. Abstract : We assessed the hypothesis that Toll‐like receptor 3 (TLR3) activation in microglia is required for neuroprotection against ischemia. After transient focal cerebral ischemia, microglia/macrophage demonstrates a reduction in TLR3 and Interleukin 6 (IL‐6). Also, oxygen–glucose deprivation (OGD) reduces TLR3 and IL‐6 expression in microglia, but polyinosinic polycytidylic acid (poly‐ICLC) rescues TLR3 and IL‐6. Importantly, conditioned media from microglia treated with poly‐ICLC protects against OGD‐induced neuron death. We propose that activation of TLR3 in microglia may promote neuron survival after ischemia.